2004
DOI: 10.1161/01.res.0000129701.14494.52
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1–Dependent Nuclear Factor of Activated T Lymphocyte Signaling Associates With Transcriptional Coactivator p300 in the Activation of the B Cell Leukemia-2 Promoter in Cardiac Myocytes

Abstract: Abstract-Endothelin-1 (ET-1) is a potent survival factor that protects cardiac myocytes from apoptosis. ET-1 induces cardiac gene transcription and protein expression of antiapoptotic B cell leukemia-2 (bcl-2) in a calcineurin-dependent manner. A cellular target of adenovirus early region 1A (E1A) oncoprotein, p300 also activates bcl-2 transcription in cardiac myocytes and is required for their survival. p300 acts as a calcineurin-regulated nuclear factors of activated T lymphocytes (NFATc), downstream targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…However, these data do not rule out the possible redundant and compensative roles of GATA-6 during LV remodeling after MI. In addition, p300 is able to interact not only with GATA-4 15,20 but also with other hypertrophy-responsive transcription factors such as myocyte enhancing factor-2, 27 nuclear factor of activated T-lymphocyte, 28 and AP-1. 29 Our findings might be applicable to these factors as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, these data do not rule out the possible redundant and compensative roles of GATA-6 during LV remodeling after MI. In addition, p300 is able to interact not only with GATA-4 15,20 but also with other hypertrophy-responsive transcription factors such as myocyte enhancing factor-2, 27 nuclear factor of activated T-lymphocyte, 28 and AP-1. 29 Our findings might be applicable to these factors as well.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Ca 2ϩ sparks on the regulation of transcription factors in PASMCs has not been examined. However, since ET-1 is a potent mitogenic agonist involved in pulmonary vascular remodeling in pulmonary hypertension (7,22) and is known to activate NFAT and other Ca 2ϩ -sensitive transcription factors (28,47) that mediate vascular cell proliferation, it is possible that Ca 2ϩ sparks originating in the perinuclear regions may be involved in the regulation of gene expressions in PASMCs, perhaps in pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,60 In clinic, efficacy and safety of endothelin-receptor antagonist has been confirmed in PAH patients. [61][62][63][64] Because ET-1 (upregulated in PAH) activates NFATc1, which in turn increases bcl ¡ 2 expression, contributing to the prosurvival and antiapoptotic effects of ET-1, 65 endothelin-receptor antagonist might also inhibit NFAT activation. At present, most of studies found that interventions targeting NFAT pathway may be effective for PAH therapy.…”
Section: Targeting the Nfat Pathway For Pah Therapymentioning
confidence: 99%